2008
DOI: 10.1111/j.1349-7006.2008.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RUNX3 in salivary adenoid cystic carcinoma: Implications for tumor progression and prognosis

Abstract: Runt-related transcription factor-3 (RUNX3), being a tumor suppressor gene in gastric cancer, plays an important role in inhibiting cellular growth by participating in the transforming growth factor-beta-dependent apoptosis. The aim of this study was to determine the expression of RUNX3 in normal salivary glands and adenoid cystic carcinomas (ACCs), comparing the results with clinicopathological factors and patient survival. The quantitative reverse transcription-polymerase chain reaction (RT-PCR) analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…adenoid cystic carcinoma is a salivary tumour in which genetic abnormalities were studied. Jian Fen He 15 and sasahira 16 found a negative correlation between the expression of the rUNX3 suppressor gene and its prognosis. This tumour, like some other salivary carcinomas, is associated with increased but prognostically irrelevant expression of the c-kit oncoprotein and eGFr (ref.…”
Section: Genetic Abnormalities In Salivary Tumoursmentioning
confidence: 99%
“…adenoid cystic carcinoma is a salivary tumour in which genetic abnormalities were studied. Jian Fen He 15 and sasahira 16 found a negative correlation between the expression of the rUNX3 suppressor gene and its prognosis. This tumour, like some other salivary carcinomas, is associated with increased but prognostically irrelevant expression of the c-kit oncoprotein and eGFr (ref.…”
Section: Genetic Abnormalities In Salivary Tumoursmentioning
confidence: 99%
“…4,5 Although the 5-year survival rate is high for patients with SACC, probably because of the slow growth of the tumor, the 10-and 15-year prognoses are poor because of the frequent local recurrences and distant metastases. [6][7][8] Although multiple genetic and epigenetic alterations have been detected in SACC, 3,[9][10][11][12][13] the precise molecular mechanisms of progression and metastasis of SACC remain unknown.…”
mentioning
confidence: 99%
“…1,2 SACC is characterized by slow but aggressive growth, nerve and blood vessel invasion, multiple recurrences, and distant metastases. [3][4][5] Lung metastasis and nerve metastasis are the biological characteristics of SACC. [6][7][8] It has been reported that the incidence of SACC with distant metastasis ranged from 35 to 50% of all cases.…”
mentioning
confidence: 99%
“…Meanwhile, in the cox multivariate survival analysis, there was significant association between rUnX3 methylation and overall survival (p=0.011). therefore, RUNX3 may be a candidate as a prognostic marker and a molecular therapeutic target for salivary Acc, providing a new approach for the diagnosis and treatment of Acc (58). this trend warrants further investigation and statistical evaluation in a larger series of patients with a longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%